ISOLATION OF MYCOPLASMAS FROM EQUINE IN BAGHDAD AREA - Al-Safar , Abdul S.; N.Al-Shammari, Abdul J. (The Iraqi Journal of Veterinary Medicine, 1986)
Out of 225 specimences taken from nasal, Vaginal, eye swabs, milk synovial fluid and from internal organsof horses. Twelve isolates were recovered as follows 9 isolates from nasal swabs, 3 isolates from vaginal swabs. No mycoplasma isolates were recovered from milk and internal orgxuns. All isolates have been tested for thier reversion to bacterial form. These isolates were purified and biochemical characterized. Six isolates “were fermented glucose, two isolates were diaminted arginine and non of these isolates did reduced tetrazolium. Six of these isolates were resistant to digitonin while the rest were sensitive.